1985
DOI: 10.1073/pnas.82.4.1271
|View full text |Cite
|
Sign up to set email alerts
|

NH2-terminal specificity and axonal localization of adrenocorticotropin binding sites in rat median eminence.

Abstract: Adrenocorticotropin binding sites in the rat median eminence have been localized in vivo. These binding sites occur in the basalar zone, which is rich in axonal endings. Using competitive binding and quantitative light-microscope radioautography, we found that the median-eminence binding site, in contradistinction to the adrenal receptor, binds specifically the residue 4-10 region of the adrenocorticotropin molecule. Using quantitative electron-microscope radioautography and median-eminence deafferentation, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…It has been shown previously that ether stress-induced release of ACTH can be blocked by microinjection of a-MSH and ACTH into the third ventricle of male rats [16]. Furthermore, CRF release from median eminence in vitro was inhibited by ACTH and related peptides [17], down to 1-24 residues, while a-MSH^^ was much less potent [18]; the latter is consistent with our results which show greater potency of ACTH|_24 over a-MSH j_i3.…”
Section: Discussionsupporting
confidence: 82%
“…It has been shown previously that ether stress-induced release of ACTH can be blocked by microinjection of a-MSH and ACTH into the third ventricle of male rats [16]. Furthermore, CRF release from median eminence in vitro was inhibited by ACTH and related peptides [17], down to 1-24 residues, while a-MSH^^ was much less potent [18]; the latter is consistent with our results which show greater potency of ACTH|_24 over a-MSH j_i3.…”
Section: Discussionsupporting
confidence: 82%
“…Hypophysiotropic axons in the rat median eminence contain large amounts of µ opioid receptors (Abbadie et al, ) that bind β‐endorphin, and tanycyte‐derived β‐endorphin would be the best positioned ligand to access these receptors. In addition, radioligand binding studies demonstrated that hypophysiotropic axons in the median eminence bind ACTH with high affinity (van Houten et al, ). This is probably due to the presence of melanocortin 4 receptors that hypophysiotropic neurons express (Tatro, ; Kishi et al, ), although the axonal presence of these receptor proteins remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, unilateral transection of the lateral retrochiasmatic area (see Fig. 4), decreased the binding of radiolabeled ACTH on the side of the ME ipsilateral to the lesion (203). These data suggest that the ACTH binding sites may be located in hypophysiotrophic CRF neurons.…”
Section: Fine Structure and Synoptic Regulation Of Crf Neuronsmentioning
confidence: 94%
“…Interestingly, the specificity of ACTH binding sites in the ME seems to show some parallelism with the potencies of ACTH-related peptides to inhibit the release of CRF-41 (202): ACTH fragments down to residues 1-24 are fully active, while a-MSH (i.e. ACTHi_i 3 ) is much less potent (203). Furthermore, unilateral transection of the lateral retrochiasmatic area (see Fig.…”
Section: Fine Structure and Synoptic Regulation Of Crf Neuronsmentioning
confidence: 95%